The mechanism of roadway formation by pressure relief of advanced gas-tangent of hard roof. (25th March 2023) - Liu, Zhao; Xu, Wentao; Li, Zhuonan
In order to explore the stability of the surrounding rock of top-cut pressure relief roadway, firstly, the failure energy release and dynamic load models of the overburden cantilever beam were established according to different crustal stress field and the structural evolution characteristics of the surrounding rock were analysed. Secondly, the mechanical model of the hard hanging roof of gob-side entry is established and the stress evolution characteristics of surrounding rock are analysed. Thirdly, the key parameters of pressure relief of gas phase cutting the top, such as hole spacing, cutting height, and cutting angle, were determined by numerical analysis. Finally, the pressure relief scheme and parameters of gas cutting top were optimised and industrial tests were carried out. The research provides theoretical guidance for the stability study of the hard roof cutting roof and decompressing into the surrounding rock of the alley and has reference significance for engineering.